Islamic Personality in Contemporary Society: Interpretative Phenomenological Analysis - Muhammad Jamaluddin; Siti Mahmudah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Islamic personality can be understood as a psychological and spiritual construct that develops through value internalization, self-reflection, and lived experience; however, how individuals construct and interpret it in everyday life remains insufficiently explored from a subjective perspective. This study aims to examine the processes of construction, internalization, and meaning-making of Islamic personality and its role in shaping moral identity, self-regulation, and life orientation. A qualitative approach using Interpretative Phenomenological Analysis (IPA) was employed to capture in-depth subjective experiences. A total of 10 participants were selected purposively based on their active engagement in religious practice and reflective awareness. Data were collected through semi-structured in-depth interviews and analyzed systematically through coding, identification of emergent themes, and development of superordinate themes. The findings reveal that Islamic personality develops as a dynamic process involving the internalization of moral and spiritual values, integration of belief and behavior, strengthening of self-regulation, construction of existential meaning, and enhancement of psychological resilience and emotional stability. It also functions as an identity framework that provides direction, coherence, and consistency in navigating contemporary life challenges. These findings highlight its role in supporting identity development, psychological well-being, and moral integrity, while offering a conceptual basis for spiritually integrated interventions, character education, and value-based counseling approaches.Kepribadian Islam dapat dipahami sebagai suatu konstruksi psikologis dan spiritual yang berkembang melalui internalisasi nilai, refleksi diri, dan pengalaman hidup; namun, bagaimana individu membangun dan memaknainya dalam kehidupan sehari-hari masih belum banyak dieksplorasi dari perspektif subjektif. Penelitian ini bertujuan untuk mengkaji proses konstruksi, internalisasi, dan pemaknaan kepribadian Islam serta perannya dalam membentuk identitas moral, regulasi diri, dan orientasi hidup. Pendekatan kualitatif dengan menggunakan Interpretative Phenomenological Analysis (IPA) digunakan untuk menangkap pengalaman subjektif secara mendalam. Sebanyak 10 partisipan dipilih secara purposive berdasarkan keterlibatan aktif mereka dalam praktik keagamaan dan kesadaran reflektif. Data dikumpulkan melalui wawancara mendalam semi-terstruktur dan dianalisis secara sistematis melalui proses pengodean, identifikasi tema-tema yang muncul, serta pengembangan tema-tema utama. Hasil penelitian menunjukkan bahwa kepribadian Islam berkembang sebagai proses dinamis yang melibatkan internalisasi nilai moral dan spiritual, integrasi antara keyakinan dan perilaku, penguatan regulasi diri, konstruksi makna eksistensial, serta peningkatan ketahanan psikologis dan stabilitas emosional. Selain itu, kepribadian Islam juga berfungsi sebagai kerangka identitas yang memberikan arah, koherensi, dan konsistensi dalam menghadapi tantangan kehidupan kontemporer. Temuan ini menegaskan perannya dalam mendukung perkembangan identitas, kesejahteraan psikologis, dan integritas moral, sekaligus menawarkan dasar konseptual bagi intervensi yang terintegrasi secara spiritual, pendidikan karakter, dan pendekatan konseling berbasis nilai.